DYNAMIC BEHAVIOR OF PREDATOR-PREY WITH RATIO DEPENDENT, REFUGE IN PREY AND HARVEST FROM PREDATOR - Hakim, Lukman; Habibi, Azwar Riza (ZERO: Jurnal Sains, Matematika dan Terapan, 2019)
Abstract In this paper, we discuss a dynamical behavior of Predator-Prey with ratiodependent, refuge in prey, and harvest from predator. Model reconstruction isorganized by adding the refuge control in prey with the values 0  m  1, and linearpredator harvesting. The aim of analysis is to describe the equilibrium points andtheir stability. In analysis, the possible fixed points are the prey extinction, thepredator extinction, and predator-prey coexists. By using linearization, thestability of predator extinction point is unstable, and the prey extinction point,coexists point becomes stable with certain condition. Finally, the dynamicalsimulation show that the trajectories of solution convergent to their stability, andthe refuge strategy suitable to avoid the extinction of prey.Key Word: Dynamic Behavior, Predator-Prey, Predation, Refuges, Harvest